“Thus, the essence of art would be the laying-into-work of the truth of being.” The figure of César Manrique and his artistic creations (Ars inspiratio: Studies dedicated to Professor Eleonora Jedlińska, 2024)
This text presents César Manrique, a lesser-known in Poland Canarian visual artist who played a significant role in the Spanish abstract art movement El Informalismo. Initially, Manrique, alongside other notable artists, experimented in his paintings with the properties of matter. After international travels, he returned in 1968 to his hometown of Arrecife, and there his focus shifted towards preserving the natural landscape. Manrique fought to maintain the unique low-rise coastal buildings and traditional viticulture in Lanzarote. Some of his notable projects on the island include a house in the dried-up Taro de Tahiche stream, the Jameos del Agua Grotto, the Mirador del Rio, the El Diablo restaurant, the Meliá Salina Hotel garden & pools, and the Jardin de Cactus. His contribution to the preservation of Lanzarote’s cultural heritage was recognized with the Europa Nostra Award in 1986.